From Picasso to Abstraction. - Robertson, Bryan (London : Annely Juda Fine Art, 1989)
Arp, Hans (Jean) ; Bergmann-Michel, Ella ; Braque, Georges ; Calder, Alexander ; Caro, Anthony ; Domela, César ; Dubuffet, Jean ; Francis, Sam ; Freundlich, Otto ; Gabo, Naum ; Gleizes, Albert ; Green, Alan ; Hall, Nigel ; Held, Al ; Henri, Florence ; Hepworth, Barbara ; Honegger, Gottfried ; Hoyland, John ; Hughes, Malcolm ; Kliun, Ivan ; Kupka, Frantisek ; Leapman, Edwina ; Leger, Fernand ; Lissitzky, El ; Malevich, Kasimir ; Man Ray ; Mansurov, Pavel ; Martin, Kenneth ; Martin, Mary ; McLaughlin, John ; Michel, Robert ; Miro, Joan ; Moholy-Nagy, Laszlo ; Moore, Henry ; Morellet, François ; Motherwell, Robert ; Nicholson, Ben ; Pasmore, Victor ; Picasso, Pablo ; Popova, Liubov ; Reynolds, Alan ; Rodchenko, Alexander ; Schwitters, Kurt ; Turnbull, William ; Vordemberge-Gildewart, Friedrich
Engels
From Picasso to Abstraction, Annely Juda Fine Art, London, 29 June - 23 September 1989
boek